Effects of controlled-release urea combined with fulvic acid on soil inorganic nitrogen, leaf senescence and yield of cotton - Geng, Jibiao (Sci Rep, 2020)
A split-plot field experiment was conducted in 2018–2019 to study the effects of nitrogen fertilizer types and fulvic acid (FA) rates on soil nitrogen and cotton growth. The nitrogen fertilizers included controlled-release urea (CRU) and urea, which were applied combined with three FA rates (90, 180 and 270 kg ha(-1)). The main plot was the nitrogen fertilizer type, and the subplot was the FA rate. The results showed that the lint yield of the FA180 treatment was 5.2–8.6% higher than the FA90 and FA270 treatments. Moreover, moderate FA application markedly improved the cotton leaf SPAD value (chlorophyll relative value), photosynthesis and chlorophyll fluorescence parameters compared with low and high FA rates. Replacing urea with CRU significantly increased the soil inorganic nitrogen and nitrogen use efficiency and also improved cotton fiber quality parameters. Meanwhile, the boll weight and seed yield of the CRU treatments were 1.5–8.4% and 3.3–19.1% higher, respectively, than the urea treatments. The interaction between nitrogen type and FA rate had a positive effect on cotton growth. Thus, the application of CRU combined with 180 kg ha(-1) FA on cotton can not only improve the fiber quality and delay leaf senescence but also increase the yield and economic benefit.